Aspectos epidemiológicos da tuberculose pulmonar nos municípios de Botucatu, Conchas, São Manuel e Avaré, Estado de São Paulo, Brasil, de 1963 a 1972 - Magaldi, Cecilia [UNESP]; Dalben, Ivete [UNESP]; Pinho, Sheila Zambello de (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1976)
O diagnóstico da situação da tuberculose pulmonar nos Municípios de Botucatu, Conchas, São Manuel e Avaré, SP, Brasil, baseou-se na prevalência e risco de infecção em escolares de lª série, em 1972, e em dados de morbidade e mortalidade específica, de 1963 a 1972. Realizou-se inquérito tuberculínico em 2.913 escolares, com PPD 23 RT-2UT; foram analisados os prontuários de 718 casos inscritos no CSI de Botucatu e os atestados de óbito de residentes, incluindo-se os ocorridos em hospitais especializados. As taxas de prevalência de infecção para os quatro Municípios foram respectivamente 2,4%; 6,8%; 1,9% e 4,5%. Para a idade de 7,5 anos, os riscos de infecção foram: 0,27%; 0,32; 0,20% e 0,34%. O nível de infecção apurado caracterizou o conjunto como área de média prevalência da tuberculose pulmonar. Os índices de prevalência de infecção relacionaram-se diretamente à incidência de casos bacilíferos de cada Município. em 530 casos com baciloscopia, houve 62,0% de positividade. As formas radiológicas moderada e avançada predominaram principalmente em adultos jovens do sexo masculino. Foram registradas alta taxa de abandono (39,5%}, baixo percentual de cura (17,9%) e 3,4% de óbitos; ao redor de 32,0% estava em tratamento. Não houve diferenças estatisticamente significativas das proporções de abandono, segundo procedência por Município ou formas da doença. Invocaram-se razões técnico-administrativas do sistema vigente para explicar esses achados. A incidência média de casos confirmados, no período, foi de 35,4 em Conchas, 33,1 em Avaré, 23,7 em Botucatu e 18,5 em São Manuel (por 100.000). Com casos confirmados e suspeitos os índices foram: 57,6; 48,8; 43,8 e 35,3. Os índices médio-anuais de mortalidade, foram: 7,6 em Botucatu, 12,14 em Conchas, 5,0 em São Manuel e 18,7 em Avaré (por 100.000). Apenas em Botucatu registrou-se declínio das taxas de mortalidade de 1963 a 1972. A mortalidade específica em adultos jovens ainda era elevada, predominando no sexo masculino, principalmente em Conchas. Sublinhou-se a necessidade de descentralizar as atividades antituberculose para atingir um controle eficiente.

The diagnosis of the pulmonary tuberculosis situation in Botucatu, Conchas, São Manuel and Avaré (State of S. Paulo) was based on the study of prevalence and risk of infection, in first grade school - children, during 1972, and on morbidity and specific mortality data gathered during a ten year period, 1963 to 1972. Tuberculin survey with PPD 23 RT-2TU was carried out in 2.913 school children; 718 records from the Botucatu Public Health Center and the death certificates of residents who died in these counties or in specialized hospitals were analysed. The prevalence rates of infection for the 4 counties were respectively 2.4, 6.8, 1.9 and 4.5%. The risks of infection for 7.5 year old school-children were 0.27, 0 32, 0.20 and 0.34%. The infection level characterized these counties as constituting a medium prevalence area of pulmonary tuberculosis. The prevalence rates of infection were directly related to the incidence of smear positive cases, in all these counties. Sixty two percent (62.0) of 530 patients submitted, to direct microscopy were smear positive cases. The predominance of moderately advanced and far advanced pulmonary lesions was observed in male young adults. A high default rate (39.5), a low proportion of cure (11.9%) and death (3.4%) were observed. Thirty two percent were under treatment. There were no statistically significant differences between default cases and county procedence of default cases and extent of pulmonary lesions. These findings were attributed to the present technical and administrative health organization. The average incidence of confirmed cases during this period was 35.4 in Conchas, 33.1 in Avaré., 23.7 in Botucatu and 18.5 in São Manuel (per 100,000). The rates of confirmed and suspected cases together were: 57.6. 48.8, 43.8 and, 35.3. The average annual mortality rates were: 7.6 in Botucatu, 12.1 in Conchas, 5.0 in São Manuel and 18.7 in Avaré (in 100,000). The decreased mortality rates during 1963 to 1972 were observed only in Botucatu. Specific mortality is still high among the young male adults, specifically in Conchas. The need to incorporate the anti-tuberculosis activities in local health services, for effective control of this disease was emphasized.
Epidemiological aspects of pulmonary tuberculosis in Botucatu, Conchas, São Manuel and Avaré (State of S. Paulo), from 1963 to 1972
Keywords: Tuberculose pulmonar; Inquérito tuberculínico; Morbidade e mortalidade; Epidemiologia; Tuberculosis pulmonary; Tuberculin survey; Morbidity and mortality; Epidemiology